Challenges in Implementing Educational Media in Madrasah - MUHAMMAD AINURRIFQI (Al-Iftah: Journal of Islamic studies and society, 2024)
The purpose of this article is to identify the problems associated with the application of educational media in madrasahs. The article aims to improve the quality of learning media implementation to enhance students' understanding and effectively achieve their learning abilities. Using a literature review method, data and sources related to the topic were collected from national journals and relevant discussions. The findings reveal that major problems include the lack of creativity among teachers in creating or developing their own teaching aids and learning media, as well as the low interest of students in the commonly used learning media. Additionally, many educational institutions face issues with suboptimal learning media, such as insufficient quantity and components, poor quality, and limited accessibility. This study contributes to the improvement of educational practices by offering insights that can guide the development of more effective and engaging learning media in madrasahs, ultimately enhancing the overall quality of education and student learning outcomes. To address these issues, it is recommended that madrasahs invest in professional development for teachers to enhance their skills in creating innovative and effective learning media, increase funding to improve the quality and accessibility of educational resources, and actively involve students in the selection and development of learning media to ensure it meets their interests and needs.